2004
DOI: 10.1520/jfs2003345
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Characteristic Patterns of Postmortem Injuries

Abstract: Animal scavenging is one of the most significant causes of postmortem injuries. A large variety of scavenging animals have been reported on in previous papers. Although postmortem injuries attributable to birds are well known in the case of ”aerial burial,” the custom in Tibet, few cases of bird scavenging have been reported. In the two cases discussed herein, postmortem injuries were attributed to crows. Both cases, shared characteristic patterns of postmortem injuries, and in both cases death was attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Areas of soft tissue on Baits A and B scavenged by buzzards had a string‐like appearance, which was consistent with Asamura et al. 's description of crow scavenging of charred human remains in Japan but was more prominent in the deer legs deposited without a hide (Fig. ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Areas of soft tissue on Baits A and B scavenged by buzzards had a string‐like appearance, which was consistent with Asamura et al. 's description of crow scavenging of charred human remains in Japan but was more prominent in the deer legs deposited without a hide (Fig. ).…”
Section: Resultssupporting
confidence: 87%
“…Vertebrate scavengers can greatly modify surface deposited human remains through the disarticulation, scattering, and removal of soft tissue and skeletal elements, as well as associated personal effects. Scavenging can modify, obscure, and remove sites of trauma on both soft tissue and bone which can lead to misinterpretations of the sequence of events that led to the deposition and condition (e.g., rate of decomposition) of the remains . However, the effects of scavenging on remains will depend on several factors including the environment, scavenger species, weather conditions, main food source, home range size, intra‐ or interspecific aggression, condition and deposition of remains, and length of exposure .…”
mentioning
confidence: 99%
“…Additionally, these canid studies have identified the spatial distribution pattern of carnivore disarticulation and skeletal element dispersal, suggesting search and recovery strategies for canid-scavenged death scenes. Avian scavenging is a largely unexplored phenomenon, and is largely restricted to discussions of the effects of crow scavenging [1,15,16]. Reeves [1] examined the timing and patterning of vulture scavenging using pig models, and found that both American black vultures (Coragyps atratus) and turkey vultures (Cathartes aura) waited approximately 24 h from the point of deposition before they began to scavenge the remains.…”
Section: Introductionmentioning
confidence: 99%
“…There are records of postmortem injuries caused by rats, hamsters and dogs in corpses found indoors (Ropohl et al, 1995;Tsokos and Schulz, 1999;Roger et al, 2002). Scavenger species, however, are more frequently reported feeding on corpses placed in open field due to its easy access (Asamura et al, 2004).…”
Section: Introductionmentioning
confidence: 99%